Diplomado gerencia de proyectos ICA-DEC, UNAM. Mod. lll : “ Suministros” - Baumanis, John (My University, 1999)
Buyers may be asked to assist in the processing of invoices. If an invoice isaddressed to a buyer, forward it to the appropriate Accounts payable group. Assistance may be required for the following reasons.
Keywords: notes; organitation; administrative; project; plannig